Correction: Exploring ethical practice in NGOS on mental health research in Malawi. - Action Amos; Cristobal Guerra; Corinne Reid; Edgardo Toro; Clara Calia (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0003001.].